2022
DOI: 10.1136/bmjmed-2022-000134
|View full text |Cite
|
Sign up to set email alerts
|

Safety of ezetimibe in lipid-lowering treatment: systematic review and meta-analysis of randomised controlled trials and cohort studies

Abstract: ObjectiveTo determine the harms of ezetimibe in people who need lipid-lowering treatment.DesignSystematic review and meta-analysis.Data sourcesRandomised controlled trials and cohort studies.Eligibility criteria for selecting studiesStudies comparing ezetimibe with placebo, standard care, or other lipid-lowering agents in people who need lipid-lowering treatment with a follow-up duration of at least six months (or 24 weeks). The relative effects for potential harms of ezetimibe were pooled by use of random eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The latest evidence demonstrates the effectiveness and safety of PCSK9 inhibitors and ezetimibe in the primary and secondary prevention of CVD (17;18). Nevertheless, the stakeholders in choosing lipid-lowering drugs are beyond clinicians and patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latest evidence demonstrates the effectiveness and safety of PCSK9 inhibitors and ezetimibe in the primary and secondary prevention of CVD (17;18). Nevertheless, the stakeholders in choosing lipid-lowering drugs are beyond clinicians and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the current study did not consider the cost of the side effects, which is very different from other cost-effectiveness analyses. Nevertheless, high-quality systematic reviews demonstrated the safety of both drugs except for the injection-site reaction for PCSK9 inhibitors, which is not likely to cause additional costs (17;18). The study chose Markov model to simulate the disease development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a metaanalysis of 48 RCTs by Wang et al ezetimibe did not influence the risk of NOD (RR = 0.88; 95% CI: 0.61-1.28) [39]. Despite inconsistent data, it is worth mentioning, that ezetimibe may reverse insulin resistance, reduce lipid dysmetabolism after a meal and improve endothelial function in patients with metabolic syndrome and coronary artery disease [40].…”
Section: Ezetimibementioning
confidence: 99%
“…Score: < 7 points; 7-8 points;9-11 points The correlation between muscle symptoms and statins: Unlikely possible; Possible; Very likely cholesterol inhibitors (e.g., ezetimibe) reduce LDL-C by 15-22%, bile-acid sequestrants reduce LDL-C by 18-25%, PCSK9 inhibitors lower LDL-C by ~ 60%, and bempedoic acid reduces LDL-C by about 20% 2,71. Besides, ezetimibe, PCSK9 inhibitors, and bempedoic acid have lower rates of muscle adverse reactions.24,71,73,74 …”
mentioning
confidence: 99%